OSTEOPOROSIS IN GERIATRIC TYPE 2 DIABETES PATIENTS AT 354 MILITARY HOSPITAL IN 2020 (Vietnam Journal of Community Medicine, 2021)
Objective: To investigate the status of osteoporosis in elderly type 2 diabetic patients treated at 354 Military Hospital and some related factors. Methods: A cross-sectional descriptive study was conducted on 388 elderly patients with type 2 diabetes who visited Military Hospital 354 from July 2020 to September 2021. Result: Rate Osteoporosis in Osteoporosis is higher than in CRC (37.6% vs 11.1%). The proportion of patients with osteoporosis (at least one of the two sites) was 40.5%. Menopause over 10 years, oophorectomy are factors that increase the risk of osteoporosis in elderly women with diabetes compared with the rest. Alcohol consumption and smoking are risk factors for osteoporosis in elderly male patients with diabetes. Patients with more than 3 comorbidities had a higher rate of osteoporosis than the group with fewer comorbidities (34.6%>22.4%). %. The risk of osteoporosis was nearly 2 times higher in people who did not treat diabetes with insulin compared with the other group (OR=1,838, 95%CI: 1,155-2.912). The risk of osteoporosis is about 2 times higher in people with poor blood sugar control (OR=1,833; 95%CI: 1.155-2.912); not well controlled HbA1c (OR = 1.604; 95% CI: 1,040 - 2.474) and not well controlled (OR = 2,156; 95% CI: 1.307 - 3,557) compared with the other groups. Conclusion: The rate of osteoporosis in the group of elderly patients with type 2 diabetes is quite high, accounting for 40.5%. The risk factors for osteoporosis in the study group were menopause over 10 years, oophorectomy in women; drinking, smoking in men; patients with more than 3 comorbidities, no insulin therapy or poorly controlled diabetes.
Keywords: Osteoporosis, the elderly, type 2 diabetes.